Correlation of blood–brain barrier leakage with cerebral small vessel disease including cerebral microbleeds in Alzheimer's disease - Cheng, Zhaozhao; Dai, Linbin; Wu, Yan; Cao, Yuqin; Chai, Xianliang; Wang, Peng; Liu, Chang; Ni, Ming; Gao, Feng; Wang, Qiong; Lv, Xinyi (Frontiers in Neurology, 2023)
Background Blood–brain barrier (BBB) damage is considered an important part of Alzheimer's disease (AD) progression, and cerebral small-vessel disease (CSVD) is commonly associated with AD. However, the relationship between BBB damage, small cerebrovascular lesions, especially cerebral microbleeds (CMBs), and amyloid and tau biomarkers remains controversial. Therefore, our study aimed to further investigate their association in our cohort of patients with AD. Methods A total of 139 individuals were divided into probable AD (18F-florbetapir PET positive, n = 101) and control group (cognitively normal, n = 38). The levels of cerebrospinal fluid (CSF) and plasma t-tau, p-tau181, Aβ40, Aβ42, and albumin were measured using corresponding commercial assay kits, and the CSF/plasma albumin ratio (Qalb), an indicator of BBB dysfunction, was calculated. CSVD burden and the number of CMBs were defined using magnetic resonance imaging. Results Patients with AD had higher Qalb (p = 0.0024), higher numbers of CMBs (p = 0.03), and greater CSVD burden (p < 0.0001). In the AD group, CMBs and CSVD correlated with a higher Qalb (p = 0.03), and the numbers of CMBs negatively correlated with CSF Aβ42 (p = 0.02). Conclusion Blood–brain barrier damage was accompanied by a more severe burden of CSVD, including CMB, in patients with AD.